1980
DOI: 10.1002/pol.1980.180181103
|View full text |Cite
|
Sign up to set email alerts
|

Melting and crystallization of poly(ethylene terephthalate) under pressure

Abstract: A piston‐cylinder‐type high‐pressure dilatometer has been built and the effect of pressure on melting behavior of poly(ethylene terephthalate) (PET) has been studied. The melting temperature increases but the rate of change of the melting temperature decreases with increasing pressure. Poly(ethylene terephthalate) crystallized from the melt at elevated pressure and temperature was studied by thermal analysis, and wide‐angle and small‐angle x‐ray diffraction and electron microscopy. Chain‐extended PET crystals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 39 publications
1
31
1
Order By: Relevance
“…On the other hand, high pressure crystallization of i-PP leads to formation of the orthorhombic c-form instead of the most usual a-monoclinic structure [10,11]. Extended-chain morphologies similar to those of HDPE were also found in PET and PA6 crystallized under elevated pressure [12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 97%
“…On the other hand, high pressure crystallization of i-PP leads to formation of the orthorhombic c-form instead of the most usual a-monoclinic structure [10,11]. Extended-chain morphologies similar to those of HDPE were also found in PET and PA6 crystallized under elevated pressure [12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 97%
“…This showed that no new crystal structure was formed at high pressure, which was consistent with the reports of the former investigators. [7][8][9][10] The melting point (T m ), melting enthalpy (H m ), and crystallinity (X c ), obtained with DSC, were also listed in Table I. Each of the samples had one melting peak and the melting points and crystallinities were much higher than those of the original material (527 K, 38%).…”
Section: Methodsmentioning
confidence: 99%
“…Based on the results of differential scanning calorimetry (DSC), small-angle X-ray scattering and electron microscopy, Siegmann et al 7 reported that extended-chain crystals of poly(ethylene terephthalate) (PET) can be formed at high pressure. However, all results of the proceeding, investigators did not confirm Siegmann's result.…”
Section: Introductionmentioning
confidence: 99%
“…By annealing, the equilibrium melting temperature of PET was originally considered to be 280 • C. [27] However, Roland et al [6] annealed PET at high temperature, resulting in a crystalline phase stable to 10 • C higher than the temperature previously regarded as the equilibrium melting point. Siegmann and Harget [28] reported that extended-chain crystals as thick as 100 nm could be formed under high pressure. Li et al [29] proposed a new mechanism in which transesterification could promote PET crystallization and improve the formation of extended-chain crystals under high pressure.…”
Section: Introductionmentioning
confidence: 99%